2020
DOI: 10.36076/ppj.2020/23/507
|View full text |Cite
|
Sign up to set email alerts
|

Ashi Acupuncture Versus Local Anesthetic Trigger Point Injections in the Treatment of Abdominal Myofascial Pain Syndrome: A Randomized Clinical Trial

Abstract: Background: Chronic pelvic pain (CPP) is defined as recurrent or continuous pain in the lower abdomen or pelvis, non-menstrual or non-cyclic, lasting at least 6 months. There is strong evidence that up to 85% of patients with CPP have serious dysfunction of the musculoskeletal system, including abdominal myofascial syndrome (AMPS). AMPS is characterized as deep abdominal pain, originating from hyperirritable trigger points, usually located within a musculoskeletal range or its fascia of coating. In the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Previous studies indicated that moxibustion on ST36 and BL23 had promising antiarthritic effects, 18 and stimulating A-Shi points could play an analgesic role. 39 , 40 Therefore, the three acupoints were selected in this study, embodied the principle of treating both symptoms and root causes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that moxibustion on ST36 and BL23 had promising antiarthritic effects, 18 and stimulating A-Shi points could play an analgesic role. 39 , 40 Therefore, the three acupoints were selected in this study, embodied the principle of treating both symptoms and root causes.…”
Section: Discussionmentioning
confidence: 99%
“…[43] Another randomized sham-controlled trial also showed that Japanese-style acupuncture is safe, effective, and non-addictive for treating endometriosis-related pelvic pain in women. [44] Studies also indicate that Ashi acupuncture is as effective as local anesthetic injections in easing pain in women with CPP, [41] and manual acupuncture plus usual care is more acceptable, safe, and effective than usual care alone. [45] In addition, a randomized controlled trial concluded that neurogenic acupoint cupping, a traditional antient treatment, could significantly reduce inflammation, pelvic pain, and improve quality of life in women with CPP.…”
Section: Psychotherapymentioning
confidence: 99%
“…[1] The mechanism of acupuncture analgesia is not clear, but studies have shown that neuroendocrine, immunological, and cardiovascular reactions can be triggered by acupuncture that penetrates the peripheral system, producing mechanical signals and generating cascaded effect. [40,41] Acupuncture can balance homeostasis by stimulating sympathetic neurons and somatic afferent fibers of neurons. [41] Acupuncture can also form a cutaneous microcurrent to promote tissue growth.…”
Section: Psychotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 85% of women with CPP have musculoskeletal associated disorders; myofascial pain syndrome can be managed, among other strategies, by trigger point anesthetic injections, therapeutic ultrasound 11 and also by acupuncture. 12 Despite the lack of robust evidence, some studies show beneficial effects of acupuncture in the treatment of these conditions. 12 Physical exercise is another domain that should be addressed and encouraged.…”
mentioning
confidence: 99%